Reduction of π-expanded cyclooctatetraene with lithium: stabilization of the tetra-anion through internal Li+ coordination - Zhou, Zheng; Zhu, Yikun; Wei, Zheng; Bergner, John; Neiß, Christian; Doloczki, Susanne; Görling, Andreas; Kivala, Milan; Petrukhina, Marina A. (Angewandte Chemie. International edition, 2021)
The chemical reduction of a π-expanded polycyclic framework comprising a cyclooctatetraene moiety, octaphenyltetrabenzocyclooctatetraene, with lithium metal readily affords the corresponding tetra-anion instead of the expected aromatic dianion. As revealed by X-ray crystallography, the highly contorted tetra-anion is stabilized by coordination of two internally bound Li+, while two external cations remain solvent separated. The variable-temperature 7Li NMR spectra in THF confirm the presence of three types of Li+ ions and clearly differentiate internal binding, consistent with the crystal structure. Density-functional theory calculations suggest that the formation of the highly charged tetra-reduced carbanion is stabilized through Li+ coordination under the applied experimental conditions.